Influence of steam jet-cooking on the rheological properties of dry and wet cationized starch solutions. (1st June 2022) - Gabriel, Martin; Gomernik, Florian; Ferstl, Esther; Chemelli, Angela; Kádár, Roland; Spirk, Stefan
Abstract: Steam jet-cooking allows for efficient dissolution of cationic starch in paper production as it operates above the boiling point of water at elevated pressures. However, the processes involved during jet-cooking and its consequences on dissolution and finally paper properties have not been fully resolved so far. As cationic starch is the most important paper additive in the wet end, any energy or material savings during dissolution will enhance the ecologic and economic performance of a paper mill. Here, we address the topic of solubilization of four different industrially relevant cationic starches processed via steam jet-cooking. We showcase that rheology is a useful tool to assess the solubility state of starches. Some starches featured liquid-like rheological behavior (loss moduli, G", greater than storage moduli, G' ) in linear viscoelastic tests and anti-thixotropic behavior in hysteresis loop tests. In contrast, cationic corn starches exhibited gel-like behavior ( G' > G″ ) and negligible hysteresis directly after cooking. Hypotheses: To evaluate the decisive factors for complete dissolution of industrial cationic starches using jet-cooking and to correlate them to rheological properties. Graphical abstract: Unlabelled Image